Study of modulation strategy for three-level active neutral point clamped inverter - Zhang, Xuecen (2019)
As renewable energy quickly penetrates into smart gird in recent decades, power converters and inverters, which perform as connection between energy and grid, have received lots of attention. Compared to 2-level inverter, multilevel inverter can generate premium power. This paper focuses on advanced active neutral point clamped (ANPC) inverter. Relevant modulation strategies are studied and one improved space vector modulation (SVM) which comprehensively considers neutral point voltage and switching loss issues is implemented through SIMULINK. Outcome indicates that this modulation has a good performance in terms of loss reduction and balancing neutral point voltage in simulation environment. It is recommended that more modulation strategies which consider different purposes can be designed to better apply ANPC inverter into industry.